Mobile Lightweight Wireless Systems Second International ICST Conference, MOBILIGHT 2010, Barcelona, Spain, May 10-12, 2010, Revised Selected Papers - Chatzimisios, Periklis.; Verikoukis, Christos.; Santamara̕, Ignacio.; Laddomada, Massimiliano.; Hoffmann, Oliver. (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2010)
This book constitutes the proceedings of the Second International ICST Conference, MOBILIGHT 2010 held in Barcelona, Spain, in May 2010. The 65 full papers presented were selected from more than 90 submissions and are organized in 3 workshops and 10 special sessions. Most of them include up-to-date results from research projects funded by the European Commission (NEWCOM++, REWIND, MIMAX, OMEGA, Self-NET, ICARUS, MOBILIA, INSPIRE). They focus on topics as mobility concepts, QoS provisions in wireless networks, advanced radio access techniques for energy-efficient communications, security and self-management in future internet wireless networks, experimental infrastructure for optimization and convergence, technologies for a converged ultra-broadband home network, advances on indoor positioning and multiuser scheduling, advanced physical layer optimization methods and user adaptive systems for mobile wireless systems.